Business Model Innovation : Past, Present, and the Future - Bashir, Makhmoor; Verma, Rajesh (Prabandhan: Indian Journal of Management, 2016)
This article provided brief insights into the current literature on business models, its components, and the relationship with other subject matters. The review brings to light the fact that despite huge surge in academic literature on business models, the concept is still underdeveloped and at a budding stage. This review also pointed out the fact that scholars still don’t have a common ground in explaining what a business model is and what are its components, but almost all scholars unanimously agreed to the fact that it is useful and practical in nature and worth of academic study. This review also highlighted that business model is altogether a different subject and is no way a sub component of strategy, innovation, or change management.